READING COMPREHENSION IN UNIVERSITY STUDENTS: AN APPROACH TO ITS DIMENSIONS FROM THE GROUNDED THEORY METHOD - Ramos, Juan David Arboleda; Ibarra, Luis Eduardo Ruano (Cadernos de Educação Tecnologia e Sociedade, 2020)
The incidence of shortcomings in reading comprehension about the academic performance of students of the Autonomous University Corporation of Cauca (Uniautónoma) and the Cooperative University of Colombia, Sede Popayán (UCC) is described. Through the qualitative method of grounded theory, a theoretical and conceptual review of the variables implicit in the problems of reading comprehension in university students is presented and an analysis of the various psychoeducational difficulties is offered, which, reflected in the institutional diagnoses and represented in the Discursive logics of students, teachers and managers, configure an intersubjective perception of the factors involved in the understanding of texts and their impact on the performance exhibited by students in the classroom. After conceptualizing the qualitative descriptive categories of the phenomenon, the work concludes with the formulation of some psycho-pedagogical strategies that contribute to reduce the academic difficulties linked to the low levels of reading comprehension evidenced in students of the two universities under study.